Prevention of Chilling Injury in Pomegranates Revisited: Pre- and Post-Harvest Factors, Mode of Actions, and Technologies Involved - Mahshad Maghoumi; Maria Luisa Amodio; Luis Cisneros-Zevallos; Giancarlo Colelli (Foods, 2023)
The storage life of pomegranate fruit (Punica granatum L.) is limited by decay, chilling injury, weight loss, and husk scald. In particular, chilling injury (CI) limits pomegranate long-term storage at chilling temperatures. CI manifests as skin browning that expands randomly with surface spots, albedo brown discoloration, and changes in aril colors from red to brown discoloration during handling or storage (6–8 weeks) at <5–7 °C. Since CI symptoms affect external and internal appearance, it significantly reduces pomegranate fruit marketability. Several postharvest treatments have been proposed to prevent CI, including atmospheric modifications (MA), heat treatments (HT), coatings, use of polyamines (PAs), salicylic acid (SA), jasmonates (JA), melatonin and glycine betaine (GB), among others. There is no complete understanding of the etiology and biochemistry of CI, however, a hypothetical model proposed herein indicates that oxidative stress plays a key role, which alters cell membrane functionality and integrity and alters protein/enzyme biosynthesis associated with chilling injury symptoms. This review discusses the hypothesized mechanism of CI based on recent research, its association to postharvest treatments, and their possible targets. It also indicates that the proposed mode of action model can be used to combine treatments in a hurdle synergistic or additive approach or as the basis for novel technological developments.